Desastres naturais sobre a Amazônia e Nordeste brasileiro associados às enchentes e inundações: o caso de 2009 - LEAL, Shirlen Viana (2019)
Reports the mapping of the natural disasters associated with floods observed in the Amazon and Northeast Brazil (NEB) regions, during the 2009 summer and autumn, as well as describes the climatic analysis of the mechanisms of large-scale. During this period, the climatology of these regions is characterized by intense and prolonged precipitation, a period known as the rainy season. Due to lack of local infrastructure and the urban planning, some cities in the Amazon NEB become risk areas during the months of the rainy season when the river level rise and cause floods. In particular, during the year 2009, the disasters triggered by floods result in a great number of publications in Official Journal, with several cities declaring emergency and calamity situations. The presence of La Niña over the Pacific Ocean and the phase of the positive dipole over the tropical Atlantic Ocean favor the activity of the ITCZ and SACZ. These interactions between the mechanisms of large-scale climatic atmosphere and ocean-atmospheric systems contributed to the heavy rains in much of the Amazon and NEB for the period January to May 2009, which justifies practically associated with the region's vulnerability to occurrence of natural disasters in this region.